Association Between Meal Skipping and Premenstrual Syndrome Among Young Females: Meal Skipping and Premenstrual Syndrome - Malik, Rimsha; Anwar, Isha; Ikram, Mashta (Pakistan Journal of Health Sciences, 2025)
Premenstrual syndrome (PMS) is the combination of physical, emotional, psychological and behavioural issues related to many symptoms. Due to which female are unable to perform their tasks. Somehow, PMS is linked with poor eating patterns and lifestyle. Modification in these things has seen lower prevalence in young female. Objective: To check the association between meal skipping and PMS in young females. Methods: A cross-sectional study was conducted among young female of the age group 18 to 30 at different educational institutions in Lahore. The target sample size of the study was 400 female. The data were gathered using a questionnaire sampling technique. A self-administered meal skipping questionnaire was used to check the dietary pattern, while the Premenstrual Syndrome Scale (PMSS) was used to examine the presence of PMS symptoms. After data collection, statistical analysis was done to find the results. Results: The p-value was 0.016, which was a significant level that indicates a positive association between PMS and meal skipping. Research revealed a significant link (p=0.016) between skipping meals and the severity of PMS symptoms, implying that dietary habits may influence symptom intensity. Conclusions: It was concluded that young adults, especially female, skip meals more frequently due to various reasons, which causes major health issues. It was seen that female who skip meals regularly have a more prominent association with premenstrual syndrome.